Avoiding the cum hoc ergo propter hoc fallacy: Comments and questions regarding Full Transfer Potential. (July 2021) - González Alonso, Jorge; Rothman, Jason
In this commentary to Westergaard (2021), we focus on two main questions. The first, and most important, is what type of L3 data may be construed as supporting evidence–as opposed to a compatible outcome–for the Linguistic Proximity Model. In this regard, we highlight a number of areas in which it remains difficult to derive testable predictions from the model that go beyond compatibility with multiple outcomes that should, in principle, be mutually exclusive. The second part of this commentary deals with Westergaard's (2021) a priori questioning of wholesale transfer as a tenable hypothesis on the basis of it creating a context for massive unlearning, both in L2 and L3 acquisition, when humans seem to display conservative learning traits from L1 acquisition already. We argue here that decades of accumulated empirical data in L2 and L3 studies have shown enough evidence of L1 transfer and restructuring to render this argument a non sequitur . In connection to this, we discuss some of the issues related to adaptive accounts of linguistic transfer across instances of language acquisition.